Belt and road initiative in world politics - Baichorov, Aleksandr M. (Journal of the Belarusian State University. International Relations, 2019)
The article provides an overview of the Chinese Belt and Road Initiative (BRI), analyzing the reasons of its introduction, the problems of its implementation and its role in world politics. The following topics are addressed: the evolution of world politics in the XXI century that created the necessary preconditions for the BRI; the reasons and problems of the BRI-Eurasian Economic Union conjugation; the ambivalent attitude of the European Union towards the BRI; India’s and Japan’s problems with the BRI; the US policies towards the PRC; the prospects for the further development of the BRI.
Keywords: Belt and Road Initiative; world politics; Eurasian Economiс Union; Russia; China; Japan; India; European Union; USA; Transpacific Partnership; Transatlantic Trade and Investment Partnership; Free Trade Area; conjugation